2017
DOI: 10.1186/s13578-017-0194-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-124 promotes proliferation and differentiation of neuronal stem cells through inactivating Notch pathway

Abstract: BackgroundNeural stem cells (NSCs) are able to differentiate into neurons and astroglia. miRNAs have been demonstrated to be involved in NSC self-renewal, proliferation and differentiation. However, the exact role of miR-124 in the development of NSCs and its underlying mechanism remain to be explored.MethodsPrimary NSCs were isolated from embryos of Wistar rats. Immunocytochemistry was used to stain purified NSCs. miR-124, Delta-like 4 (DLL4), ki-67, Nestin, β-tubulin III, glial fibrillary acidic protein (GFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…More data demonstrated that miR‐124 promoted neuronal differentiation of and neurite outgrowth in mouse inner ear neural stem cells (NSCs) by regulating tropomyosin receptor kinase B (TrkB) and cell division control protein 42 homolog (Cdc42) . Another study also elucidated that miR‐124 promoted neural differentiation of NSCs by directly targeting DLL4 through suppression of the Notch pathway . Some scholars have suggested that Lhx2 is a primary target gene of miR‐124a and that Lhx2 downregulation by miR‐124a is required for the prevention of apoptosis in the developing retina and for proper axonal development of hippocampal neurons .…”
Section: Mir‐124 In Metabolism and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More data demonstrated that miR‐124 promoted neuronal differentiation of and neurite outgrowth in mouse inner ear neural stem cells (NSCs) by regulating tropomyosin receptor kinase B (TrkB) and cell division control protein 42 homolog (Cdc42) . Another study also elucidated that miR‐124 promoted neural differentiation of NSCs by directly targeting DLL4 through suppression of the Notch pathway . Some scholars have suggested that Lhx2 is a primary target gene of miR‐124a and that Lhx2 downregulation by miR‐124a is required for the prevention of apoptosis in the developing retina and for proper axonal development of hippocampal neurons .…”
Section: Mir‐124 In Metabolism and Developmentmentioning
confidence: 99%
“…34 Another study also elucidated that miR-124 promoted neural differentiation of NSCs by directly targeting DLL4 through suppression of the Notch pathway. 38 Some scholars have suggested that Lhx2 is a primary target gene of miR-124a and that Lhx2 downregulation by miR-124a is required for the prevention of apoptosis in the developing retina and for proper axonal development of hippocampal neurons. 39 Kaili Liu et al showed that NeuroD1 could act as a direct target of miR-124 in vivo to control Xenopus cell proliferation and neurogenesis.…”
Section: And Developmentmentioning
confidence: 99%
“…MMP9 functions as a transcription factor, which can bind to and inhibit the Notch1 signaling pathway (Bin Hafeez et al, ). The Notch signaling pathway is an evolutionarily highly conserved signaling pathway which plays an important role in serval biological processes, such as cell proliferation, differentiation and apoptosis (Jiao, Liu, Yao, & Teng, ). In mammals, there are four Notch receptors (Notch1, 2, 3, 4), and upon binding by a membrane bound ligand on a neighboring cell, the Notch receptors undergo proteolytic cleavages leading to the release of the Notch intracellular domain (Zou, Luo, & Xiang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Distruption of miR-124 results in neural abnormalities, indicating that miR-124 is important for the maturation and survival of dentate gyrus neurons and retinal cones (Sanuki, Onishi et al 2011). Overexpression of miR-124 promotes neuronal differentiation in a variety of neural progenitor cells, including mesenchymal, brain tumor and neuronal stem cells (Silber, Lim et al 2008, Zou, Chen et al 2014, Mondanizadeh, Arefian et al 2015, Jiang, Du et al 2016, Jiao, Liu et al 2017, Sharif, Ghahremani et al 2017, and overexpression of both miR-124 and miR-9 were sufficient to induce differentiation of neural progenitor cells and fibroblasts into neurons (Krichevsky, Sonntag et al 2006, Yoo, Sun et al 2011. miR-124 has been shown to be an important neuronal fate determinant for the neuronal stem cells in the subventricular zone (SVZ), the largest neurogenic region in the adult mammalian brain (Cheng, Pastrana et al 2009, Akerblom, Sachdeva et al 2012.…”
Section: Biology Of Mir-124mentioning
confidence: 99%
“…Moreover, SCP1 (Small C-terminal domain phosphatase 1) which is recruited by REST to RE-1 element to function as a silencer for neuronal genes in non-neuronal cells (Yeo, Lee et al 2005), is directly targeted by miR-124 on its 3' UTR during neuronal differentiation (Visvanathan, Lee et al 2007). Additionally, miR-124 also regulates neuronal differentiation through the Notch signaling pathway via repression of the Notch ligands Jag1 (Jagged1) (Cheng, Pastrana et al 2009, Liu, Chopp et al 2011) and DLL4 (Delta-like 4) (Jiao, Liu et al 2017), allowing exit from stem cell self-renewal and differentiation into neuronal cell fate.…”
Section: Biology Of Mir-124mentioning
confidence: 99%